(untitled) (Al-Qamar, 2020)
Rights of special people have been explained in the light of Islamic Sharī‘ah in this research article. Islam not only endorses the rights of special people but also makes sure that they should get them in a systematic manner also. The efforts for the grant of rights of special people reach back to a few decades in the modern age, Whereas Islam made sure that these rights are granted more than fourteen hundred years ago taking care that they should be implemented too. Special rights granted to persons with disabilities have also been discussed with regard to prayers, limitations (حدود), blood money, justice and social laws. Acknowledging their presence in society, Islam ensured the preservation of their rights and removed the problems and difficulties in the wake of granting their rights, Islam also saw to it that proper waivers be in place in the case of their not being able to meets their obligations. Islamic jurisprudents have used terms like ease(التیسیر), reduction (التخفیف),waiver(الترخیص) and flexibility(التوسعۃ) etc. for them.